Effect Evaluation of Multilevel Fuzzy Comprehensive Evaluation Mechanism Combined with Multimedia Teaching on the Cultivation of Comprehensive Quality of Vocational Students - Jin Si; Siming He (Advances in Multimedia)
The core goal of higher vocational education is to cultivate students with good professional quality. The employability of college students depends on their professional quality to a large extent. From the perspective of school education, all kinds of higher vocational colleges have entered a new level in practice, but the evaluation of comprehensive quality is still relatively weak. Therefore, in order to enhance the comprehensive ability of higher vocational students and cultivate their excellent comprehensive quality, this paper adopts the fuzzy comprehensive evaluation method and puts forward the evaluation method of the comprehensive evaluation system of higher vocational students, so as to provide reference for solving the problem of comprehensive quality evaluation. The specific process is as follows: in this paper, a two-level fuzzy mathematical model is established by using fuzzy mathematics theory and multimedia technology. First of all, according to the educational characteristics such as learning interest, psychological quality when encountering difficulties, and the ability to solve problems cooperatively, a set of secondary indicator system reflecting vocational college students is established. With this indicator, quantitative indicators are fuzzified by introducing membership functions, and a single factor evaluation matrix is established. Then, the specific steps are illustrated with examples to realize the qualitative analysis and quantitative evaluation of students’ comprehensive quality. The results show that the new comprehensive quality evaluation method established in this paper has strong practicality and innovation.